EFFORTS TO IMPROVE HR MANAGEMENT UNDER INTERNAL SUPERVISION ON VILLAGE FINANCIAL MANAGEMENT - Rapang, Nataniel (Journal for Management Student (JFMS), 2024)
Abstract Supervision of village financial management performance is carried out by the District Government and the Village Consultative Body (Law Number 6 of 2014). Mondale et al., (2017) explained that supervision of all parties, including the government, community government and law enforcement officials, plays a role in detecting opportunities for problems to arise in the implementation of village budgets. The study was conducted in 30 Desa in Sidoarjo with a total of 218 respondents who were Government Apparatus in each Village. Data was obtained from questionnaires distributed to the Village Head, Village Secretary, Village Treasurer, Head of Affairs and Members of the Consultative Body Village. The data is then analyzed by multiple linear regression.The test results show that Human Resource Capacity, Procurement of Goods and Services and Supervision together influence the absorption of the Village budget in Sidoarjo. Human Resource Capacity partially influences Village Budget Absorption. Procurement of Goods and Services has a partial effect on Village Budget Absorption and Financial Supervision influences Village Budget Absorption.